Description of two new Carlia species (Reptilia: Scincidae) from north-east Australia, elevation of Carlia pectoralis inconnexa Ingram & Covacevich 1989 to full species status, and redescription of Carlia pectoralis (de Vis 1884) - Hoskin, Conrad J.; Couper, Patrick J. (Zootaxa, 2012)
Scincid lizards belonging to the genus Carlia are found in eastern and northern Australia and in New Guinea andassociated islands. These skinks are a particularly diverse component of the reptile fauna of north-east Australia. Carliapectoralis (de Vis 1884) was formerly regarded as occurring over much of eastern Queensland, in north-east Australia.Here we show that it consists of four species: Carlia pectoralis, Carlia decora sp. nov., Carlia rubigo sp. nov. and Carliainconnexa Ingram & Covacevich 1989 (which was formerly described as a subspecies of C. pectoralis). Herein, wedescribe two new species, elevate C. p. inconnexa to full species status with a revised description, and redescribe C.pectoralis sensu stricto. The four species differ in aspects of scalation, morphology and colour pattern. Carlia decora sp.nov. occurs in vine thickets, rainforest margins and moist open forests in high rainfall coastal areas of mid-east and north-east Queensland. Carlia rubigo sp. nov. occurs in dry open forests of inland eastern Queensland and in some coastal areasof mid-eastern Queensland. Carlia pectoralis is distributed through open forests of south-east Queensland. Carliainconnexa is restricted to rocky open forests on islands of ‘the Whitsundays’ off mid-eastern Queensland. The addition of these three species brings the number of Australian Carlia to 22 species, 17 of which are found in Queensland.